Displace of Documentary Heritage from the Soviet Union to Poland during the Third Decade of the XXth Century - Hiarnovich, Tatsiana (Bibliotheca Lituana, 2014)
The paper explores the displace of Polish archives from the Soviet Union that was performed in 1920s according to the Riga Peace Treaty of 1921 and other international agreements. The aim of the research is to reconstruct the process of displace, based on the archival sources and literature. The object of the research is those documents that were preserved in the archives of Belarus and together with archives from other republics were displaced to Poland. The exploration leads to clarification of the selection of document fonds to be displaced, the actual process of movement and the explanation of the role that the archivists of Belarus performed in the history of cultural relationships between Poland and the Soviet Union. The articles of the Treaty of Riga had been formulated without taking into account the indivisibility of archive fonds that is one of the most important principles of restitution, which caused the failure of the treaty by the Soviet part.